2020
DOI: 10.3390/ijerph17207464
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery Performance and Tactile Spatial Acuity: Are They Altered in People with Frozen Shoulder?

Abstract: Frozen shoulder (adhesive capsulitis) is a severe chronic pain condition that is not well understood and current treatment is suboptimal. In several other chronic pain conditions motor imagery and tactile acuity deficits are present, which are thought to represent associated neuroplastic changes. The aims of this study were to determine if motor imagery performance assessed by the left/right judgement task, and tactile acuity assessed by two-point discrimination, are altered in people with unilateral frozen sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…The effect of back and neck pain on the LRJT performance was controversial, which was consistent with the findings of a previously published meta-analysis study [8]. Although two-point discrimination test (TPDT) was usually conducted to investigate an alterations of primary somatosensory cortex (S1) representation [37,38,40,41,[45][46][47]49,51,53] and the results of TPDT was significantly difference from the healthy participants, the relationship between the LRJT and the TPDT was not statistically significant. Therefore, it can be suggested that peripheral pain may alter both motor and sensory cortical representations, but the interaction between two representations requires a further study.…”
Section: ) Somatosensory Information (1) Proprioceptive Informationsupporting
confidence: 56%
See 1 more Smart Citation
“…The effect of back and neck pain on the LRJT performance was controversial, which was consistent with the findings of a previously published meta-analysis study [8]. Although two-point discrimination test (TPDT) was usually conducted to investigate an alterations of primary somatosensory cortex (S1) representation [37,38,40,41,[45][46][47]49,51,53] and the results of TPDT was significantly difference from the healthy participants, the relationship between the LRJT and the TPDT was not statistically significant. Therefore, it can be suggested that peripheral pain may alter both motor and sensory cortical representations, but the interaction between two representations requires a further study.…”
Section: ) Somatosensory Information (1) Proprioceptive Informationsupporting
confidence: 56%
“…Since Coslett et al [6,7] established the evidence of the effect of pain on motor imagery, the LRJT has been widely used for research in cohorts with pain. Most studies were conducted in patients with upper limb pain [37][38][39][40][41][42][43][44], including frozen shoulder, hand OA, carpal tunnel syndrome, wrist pain and lateral epicondylitis. The performance of the LRJT in patients with low limb pain [45][46][47][48], fibromyalgia [49] back and neck pain [50][51][52][53], and facial pain [54] was also investigated.…”
Section: ) Somatosensory Information (1) Proprioceptive Informationmentioning
confidence: 99%
“…Furthermore, two-point discrimination was altered in patients with frozen shoulders when compared to controls 23 or the unaffected shoulder. 22 These studies indicate altered cortical function within certain shoulder pathologies. Therefore, it could be suggested that this may also be possible in patients with GHJ instability.…”
Section: Introductionmentioning
confidence: 88%
“…Taking into account that FS is characterized by being long-lasting, it is plausible that neuroplastic changes occurring at different levels of the central nervous system might contribute to pain maintenance [ 8 ]. Apart from some preliminary research [ 9 , 10 , 11 , 12 , 13 ], the implication of central pain mechanisms in people with FS remains uncertain. On the other hand, the role of low-grade inflammation and immune system response dysregulation leading to pathological changes in the shoulder capsule is gaining interest in the scientific literature [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%